The human right to water: a state debt with the panamanian population - Díaz-Ríos, Tomás (2021)
Panama is a favored country in terms of water resources; however, it is observed that 10% of the population of the Republic lacks access to drinking water. Based on international instruments and commitments to the Millennium Development Goals and the Sustainable Development Goals of the United Nations, the “human right to drinking water” will be based on the new constitutional reforms derived from university work. The main objective of the present study is to allow legal instruments to reach, through constitutional guarantees, the most vulnerable population. Its application will be through comparative law. Employed methodology was by means of observation and analysis of secondary sources and data. The statistics provided by the Planning Directorate of the National Aqueducts and Sewers Institute (IDAAN) were used. This article is part of the research section of the doctoral thesis “The water footprint; an indicator to apply to the circularity of water: sustainable management model for Panama”. Incorporation of the text on the human right to water in the Political Constitution of the Republic of Panama will pay for the delay that the State has had with the Panamanian population, and the international agreements signed. The criteria analyzed will serve to reflect on the issues of water management and governance; and will allow advances in the matter of human rights to water, it will help advance the emphasis on the recognition of the “human right to water for Panama”.